Perchlorate and Tetrafluoroborate Complexes of Mn(II), Ni(II), Co(II), and Cu(II) with Tetrabenzo-(b,e,l, o)- 4,14-Dithia-1,7,11,17,-Tetraaza-8,10,18,20-Tetramethyl- cylodedeca-7,10,17,20-Tetraene - Shukla, P.R.; Ahmad, Nihal; K. Pathak, Ashish (Asian Journal of Chemistry, 2010)
Eight macrocyclic complexes have been prepared by the template condensation reaction between di(2-aminopenyl) sulphide and acetylacetone. These complexes have the general formula [M(L)]X2 and [M´(L)(H2O)2]X2 where L ═ tetrabenzo-(b,e,l,o)-4,14-dithia-1,7,11, 17-tetraaza-8,10,18,20-tetramethylcyclodedeca-7,10,17,20-tetraene, M ═ Ni(II), Cu(II); M´ ═ Mn(II), Co(II) and X ═ ClO4–, BF4–. The complexes have been characterized on the basis of analytical data, conductance measurements, IR, 1H NMR, magnetic and electronic spectral studies and are assigned to have either square planar or octahedral geometries.